Pengentasan Stunting dengan Pemanfaatan Sumber Daya Pangan Tempatan di Desa Sibuak, Kecamatan Tapung, Kabupaten Kampar, Provinsi Riau - Sharnuke Asrilsyak; Vanesia Hutagalung; Muhammad Aras Azdira; Sefti Eliza (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2023)
Socialization of stunting alleviation by using hydroponic is an effort to develop community awareness of stunting and reduce stunting levels by increasing knowledge and skills. Alleviating stunting is an effort to decrease growth disorders in children due to chronic malnutrition and recurrent infections, that characterized by below standard height by using a hydroponic wick system. Wick hydroponics (Wick) is a hydroponic method that uses a wick as a link between nutrients and the root part of the planting medium. The socialization was held in Sibuak , Tapung , Kampar, Riau. It was started with an explanation about stunting and the hydroponic wick system and demonstration with Pak Choy mustard , started with seeding , installing, and transplanting the hydroponic wick system and discussion. Through this activity the Sibuak villagers know about the importance of how to handle stunting and knows about hydroponic wick systems, and take care of hydroponic plants.